Asymmetric nanocomposite material of titanium dioxide-gold nanorods, preparation method and application thereof
By using asymmetric nanocomposites of titanium dioxide-gold nanorods for photothermal and photodynamic synergistic treatment in hypoxic tumors, the problem of poor photodynamic treatment of hypoxic tumors in the prior art was solved, and efficient tumor treatment was achieved and the effective application of titanium dioxide nanometers in the biological field.
Patent Information
- Application Number
- CN202011397346.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-12-02
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2040-12-02
AI Technical Summary
The prior art has poor photodynamic treatment effect in hypoxic tumors, and the application of titanium dioxide nanometers in the biological field is limited by the high electron-hole recombination rate and inappropriate excitation wavelength.
Asymmetric nanocomposite material using titanium dioxide-gold nanorods is used to form an asymmetric structure through one end of the gold nanorod as the growth point of titanium dioxide, and fluorescent molecules are modified on the surface of the composite material to improve biocompatibility and light absorption efficiency.
It has achieved efficient photothermal and photodynamic collaborative treatment in hypoxic tumors, which has improved the accuracy and effect of treatment, and at the same time solved the problem of application of titanium dioxide nano in the biological field.
Smart Images

Figure HDA0002814562870000011 
Figure HDA0002814562870000012 
Figure HDA0002814562870000013
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nanomaterials, and in particular to an asymmetric nanocomposite material of titanium dioxide-gold nanorods, a preparation method thereof, and application thereof in photothermal and photodynamic synergistic therapy of hypoxic tumors. Background Art
[0002] In recent years, near-infrared-based phototherapy technologies, mainly including photothermal therapy and photodynamic therapy, have been widely developed in tumor treatment due to their good accuracy, high efficiency, deep tissue penetration, minimally invasive surgery and few side effects. Among them, photothermal therapy uses photothermal agents (such as gold nanoparticles, polyaniline nanoparticles, carbon nanotubes, polypyrrole nanoparticles, etc.) to achieve irradiation heating of tumors through the transmission of near-infrared light for rapid ablation. However, local excessive temperature may cause heat shock reaction and damage normal tissue around the tumor. In addition, photodynamic therapy refers to the local production of reactive oxygen species by photosensitizers under light, which has also attracted great attention for the precise and effective treatment of tumors. However, considering that hypoxia is a common feature of tumors, the photodynamic effect of most photosensitizers gradually weakens with the increase of oxygen consumption at the tumor. In addition, small molecule photosensitizers have also been limiting the development of photodynamic therapy due to reasons such as rapid metabolism, photobleaching and self-oxidation. Therefore, multiple cancer treatment methods such as photothermal therapy and photodynamic therapy have their own advantages and cover each other due to their synergistic effects, which is the best choice for controllable and precise treatment of tumors.
[0003] Compared with small molecules, nanosystems are a promising strategy for tumor treatment, with advantages such as long circulation, good stability, and good passive targeting effect in the body. Titanium dioxide nanoparticles are an interesting and important photocatalyst, which has been studied and applied in the fields of catalysis and the environment due to its low toxicity, good stability, high efficiency, and low cost. Its process of generating reactive oxygen species under light without relying on oxygen can well solve the problem that many current photosensitizers have poor photodynamic effects in hypoxic tumors and has attracted widespread attention. However, its large band gap requires high-energy ultraviolet excitation and rapid recombination of electrons and holes, which has always faced great challenges in its application in the biological field. Therefore, how to reduce the electron-hole recombination rate of titanium dioxide and adjust the excitation wavelength directly or indirectly to the near-infrared range has important practical value in biological applications.
[0004] At present, gold, silver, and palladium nanoparticles with surface plasmon resonance and electron-donating molecules have been applied to promote the generation of electrons and enhance the absorption of long-wavelength light. However, there are still various problems such as the large size of the composite nanoparticles affecting the penetration at the tumor, the single photodynamic therapy mode, the low electron transfer efficiency, and the absorption of light mostly in the visible region. Therefore, the representative of photothermal materials: gold nanorods (diameter less than 15nm), with flexible and adjustable SPR absorption, high photothermal conversion efficiency, low toxicity and good electron donors can be used to regulate titanium dioxide nanoparticles. However, due to the poor growth conditions of gold nanorods, titanium dioxide nanoparticles can only be regenerated as seeds on gold nanorods. However, under uncontrolled conditions, the synthesis of well-defined spatially separated titanium dioxide on single-ended small gold nanorods by wet chemical methods is still a technical problem that needs to be solved. Summary of the invention
[0005] One of the purposes of the present invention is to provide a fluorescently modified gold nanorod and titanium dioxide asymmetric nanocomposite particles, the composite material is a composite nanoparticle used for photothermal and photodynamic synergistic therapy of hypoxic tumors; the nanocomposite particles have good tumor penetration due to their small size, absorb in the near-infrared light region of 650-900 nanometers with strong penetration, and are surface-modified with PEG and fluorescent molecules-PEG to increase biocompatibility. It can be used for suitable photothermal and good photodynamic synergistic therapy of hypoxic tumors under near-infrared illumination; the synthesis method of the nanocomposite particles has the advantages of easy operation, cheap raw materials, simple separation, etc.
[0006] One of the purposes of the present invention is to provide an asymmetric nanocomposite material of titanium dioxide and gold nanorods, wherein the nanocomposite material has one end of the gold nanorod as the growth point of titanium dioxide nanoparticles, and titanium dioxide is directly in contact with one end of the gold nanorod, and has an asymmetric structure, wherein the aspect ratio of the gold nanorod is about 2.5-3.5, and the thickness of the directly contacted titanium dioxide is 7-20 nanometers, preferably 13-20 nanometers. Under the irradiation of near-infrared light, the composite nanoparticles can transfer hot electrons on the gold nanorods through the Schottky barrier to the conduction band of titanium dioxide, and can simultaneously perform photothermal therapy and photodynamic therapy on the tumor site. The structure is as follows Figure 1 As shown:
[0007] Preferably, in the technical solution described above, the surface of the asymmetric nanocomposite material of titanium dioxide-gold nanorods is further modified by fluorescent molecules emitting at 650-900 nanometers through azo bonds.
[0008] Preferably, in the technical solution described above, the fluorescent molecules include: cyanine dyes, semi-cyanine dyes, Nile blue, methylene blue, rhodamine dyes, and more preferably fluorescent molecules emitting at 810 nanometers.
[0009] The second aspect of the present application is a method for synthesizing composite nanoparticles for photothermal and photodynamic synergistic therapy of hypoxic tumors, which specifically comprises the following steps:
[0010] (1)C 16 TAB was mixed with chloroauric acid solution, and then NaBH4 solution was injected, and the gold seed solution was obtained after standing and aging;
[0011] (2) C 16 After TAB is dissolved, silver nitrate, chloroauric acid, concentrated hydrochloric acid, and ascorbic acid are added one by one, and after stirring evenly, a gold nanorod growth solution is prepared;
[0012] (3) injecting the gold seed solution into the gold nanorod growth solution, mixing overnight and separating to obtain gold nanorods with an aspect ratio of about 2.5-3.5 and a diameter of 10-20 nanometers;
[0013] (4) NaHCO3 was added dropwise into the diluted TiCl3 solution to obtain a Ti solution, and then the gold nanorods and C 16 The TAB mixture is added to the above Ti solution for reaction to obtain a final product, which is an asymmetric structure in which the above titanium dioxide is directly grown on one end of the gold nanorod, wherein the aspect ratio of the gold nanorod is about 2.5-3.5, and the thickness of the directly contacted titanium dioxide is 7-20 nanometers, preferably 13-20 nanometers, and finally stored in C 16 TAB solution.
[0014] Preferably, in the technical solution described above, the step (1) of preparing the gold seed solution in the method comprises: adding 5-20 volumes of C 16 The TAB solution is mixed with 0.1-3 volumes of chloroauric acid solution with a concentration of 10-50 mM, and then 0.6-1.2 volumes of NaBH4 solution are quickly added under stirring, and the mixture is allowed to stand for aging to obtain a gold seed solution.
[0015] Preferably, in the technical solution described above, the step (2) of preparing the gold nanorod growth solution in the method comprises: adding a certain amount of C 16 TAB is dissolved in 50-1000 volumes of deionized water, and after cooling, 2-10 volumes of silver nitrate with a concentration of 1-10 mM are added; after stirring the mixture, 5-20 volumes of 0.5-2 mM chloroauric acid solution are added; then the mixture becomes colorless, and after stirring, 0-2 volumes of concentrated hydrochloric acid are added to adjust the pH value of the mixture; after slowly stirring, 0.2-0.8 volumes of ascorbic acid with a concentration of 40-100 mM are added, and stirred vigorously.
[0016] Preferably, for the technical solution described above, the step of preparing gold nanorods in step (3) of the method comprises: injecting 0.2-0.5 volume of the gold seed solution prepared in step (1) into the gold nanorod growth solution prepared in step (2); after a short period of intense stirring, leaving the resulting mixture overnight to obtain a gold nanorod stock solution; and centrifuging to obtain the gold nanorods.
[0017] Preferably, for the technical solution described above, the step of preparing the final product in step (4) of the method comprises: diluting 0-0.5 ml of 10-30% TiCl3 with 2-15 volumes of deoxygenated water; adding 0.5-2M NaHCO3 dropwise to the diluted TiCl3 solution under stirring; after the mixture turns into a blue solution, adding the last few drops of excess NaHCO3, centrifuging 0.1-2 volumes of the gold nanorod stock solution with deoxygenated water to dilute it to 0.1-1.8 volumes, and adding 0.1-3 volumes of 0.2M C 14 Mix the TAB solution; then add it to the above blue solution; gently stir / shake the dispersion for more than 1 hour; centrifuge and wash to obtain the final product, and store it in C 16 TAB solution.
[0018] Preferably, in the technical solution described above, in order to further accurately guide the illumination position of the near-infrared light, the surface of the final product composite nanostructure obtained in step (4) is modified by azo bonds with fluorescent molecules emitting at 650-900 nanometers.
[0019] Preferably, in the technical solution described above, the fluorescent molecules include ENBS-PEG-SH, and PEG-SH and PEG-COOH are used to modify the above-synthesized composite nanoparticles for standby use.
[0020] The third aspect of the present application is to use the composite material in a photothermal and photodynamic synergistic treatment product for hypoxic tumors.
[0021] Beneficial effects:
[0022] The asymmetric composite nanoparticles have the advantages of low-cost synthetic raw materials, simple and easy operation, and easy separation.
[0023] The composite nanoparticles are small in size, absorb in the near-infrared, and have good biocompatibility, solving various problems in the application of titanium dioxide nanoparticles in the biological field.
[0024] The asymmetric composite nanoparticles can accurately carry out appropriate photothermal and photodynamic synergistic therapy under near-infrared light on hypoxic tumors. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1Transmission electron micrographs of gold nanorods and gold nanorod-titanium dioxide asymmetric composite nanostructures, wherein: A is a transmission electron micrograph of gold nanorods, and B is a transmission electron micrograph of asymmetric composite nanostructures of gold nanorods-titanium dioxide.
[0026] Figure 2 It is an elemental scan of a gold nanorod-titanium dioxide asymmetric composite nanostructure, wherein: A is a scan of a gold nanorod-titanium dioxide asymmetric composite nanostructure, B is an elemental analysis of gold in the gold nanorod-titanium dioxide asymmetric composite nanostructure, and C is an elemental analysis of titanium in the gold nanorod-titanium dioxide asymmetric composite nanostructure.
[0027] Figure 3 Absorption diagram of gold nanorods and composite nanoparticles and potential change of asymmetric nanostructure modified PEG, where: A is the electron microscope image of gold nanorods (in water) and gold nanorod-titanium dioxide asymmetric composite nanostructure (in ethanol), B is the potential change diagram of gold nanorod-titanium dioxide asymmetric composite nanostructure during the modification process; 1: C on the surface of asymmetric composite nanostructure gold rod 16 TAB was replaced by SH-PEG; 2: Based on 1, C 16 TAB is replaced by HOOC-PEG; 3: Replace the modified fluorescent molecule PEG based on 2.
[0028] Figure 4 Photothermal performance and ESR test of active oxygen generation capacity of nanomaterials, where: A is the photothermal experiment of gold nanorods, gold nanorod-titanium dioxide asymmetric composite nanostructures and aqueous solutions, and B is the capture of active oxygen by gold nanorods and gold nanorod-titanium dioxide asymmetric composite nanostructures.
[0029] Figure 5 Temporal detection of cellular uptake of asymmetric composite nanoparticles.
[0030] Figure 6 The killing effect of asymmetric composite nanoparticles of different concentrations on human breast cancer cells under hypoxic conditions. A is that the gold nanostructure fully encapsulated by titanium dioxide has almost no killing effect on cells; B is that it has a good phototoxic effect on human breast cancer cells under hypoxic conditions;
[0031] Figure 7 It is the imaging position and time guidance of the tumor location of mice before and after the fluorescent modified asymmetric composite nanoparticles.
[0032] Figure 8 It is the photothermal imaging of tumors by nanoparticles under near-infrared laser irradiation.
[0033] Fig. 9Are the changes in tumor volume and weight of mice, where: A is the change in tumor volume of mice under different treatment conditions over time, and B is the change in weight of mice under different treatment conditions over time. DETAILED DESCRIPTION
[0034] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. The synthesis of the composite nanoparticles of the present invention is described below by way of examples (but not limited to these examples).
[0035] Example 1
[0036] A specific method for synthesizing composite nanoparticles for synergistic photothermal and photodynamic therapy of hypoxic tumors.
[0037] Synthesis of gold nanorods:
[0038] 10 Volume C 16 TAB (0.1M) solution and 0.1 volume of chloroauric acid solution (25mM) were mixed in a 20 volume reaction bottle, and then stirred evenly at room temperature, and 1 volume of freshly prepared 100mM NaBH4 solution (ice-cooled) was added and quickly injected into the solution mixture. The solution was quickly stirred for 2 minutes and allowed to stand at room temperature for aging.
[0039] 3.6 g C 16 TAB was dissolved in 100 volumes of deionized water to prepare a growth solution for gold nanorods in a 250 volume conical flask. After cooling, 5 volumes of silver nitrate (4mM) were added. The mixture was kept as it was at room temperature for 15 minutes, and then 10 volumes of chloroauric acid solution (1mM) were added. The mixture then became colorless, and after stirring evenly, 0.89 volumes of concentrated hydrochloric acid were added to adjust the pH value of the mixture. After further slow stirring, 0.50 volumes of ascorbic acid (64mM) were added, and after vigorous stirring, 0.32 volumes of gold seed solution were injected into the growth solution. After vigorous stirring again, the resulting mixture was kept as it was at room temperature for 12 hours for the growth of gold nanorods. The final product was separated by centrifugation, and the supernatant was removed ( Figure 1 ).Depend on Figure 1 A shows that the structure of the gold nanorods presents a relatively uniform morphological distribution, with an aspect ratio of about 3 and a diameter of about 10-20 nm.
[0040] Synthesis of gold nanorod-titanium dioxide asymmetric composite nanostructures:
[0041] Dilute 0.1 ml of 10-15% TiCl3 with 10 volumes of deoxygenated water in a reaction flask (different suppliers or batches may affect the subsequent dosage). Add 1M NaHCO3 dropwise to the diluted TiCl3 solution while stirring. Add the last few drops of NaHCO3 after the mixture turns into a blue solution. After that, dilute the mixture (0.8 volumes of gold nanorod stock solution centrifuged and diluted to 1.0-3.2 volumes and 1.6 volumes of 0.2M C NaHCO3 with deoxygenated water) to 10 volumes of TiCl3. 14 TAB solution was added to the above solution. The dispersion was then gently stirred / shaken for more than one hour. The product was collected by centrifuge and washed once with ethanol and then with C 16 The samples were washed once with TAB solution (0.1 M) and finally stored at C 16 TAB solution ( Figure 1 and Figure 2 ).Depend on Figure 1 B and Figure 2 It was shown that titanium dioxide was directly grown asymmetrically on a single head of a gold nanorod, and the structure was further confirmed by elemental analysis.
[0042] Modification of composite nanostructures with fluorescent molecules:
[0043] The composite nanoparticles synthesized above are modified with fluorescent molecules ENBS-PEG-SH, PEG-SH and PEG-COOH for later use.
[0044] Example 2
[0045] Synthesis of gold nanorods:
[0046] 1 Volume C 16 TAB (0.1M) solution and 0.01-0.2 volume of chloroauric acid solution (25mM) were mixed in a 20 volume reaction bottle, and then stirred at 30°C for 5 minutes, and 0.06-0.1 volume of freshly prepared 100mM NaBH4 solution (ice-cooled) was added and quickly injected into the solution mixture. The solution was rapidly stirred for 2 minutes and allowed to stand at 30°C for 30 minutes for aging.
[0047] C 16TAB was dissolved in a certain amount of deionized water (50°C) to prepare a growth solution for gold nanorods in a conical flask. After cooling to 30°C, 1 volume of silver nitrate (4mM) was added. The mixture was kept at 30°C for 15 minutes, and then 1.5-2 volumes of chloroauric acid solution (1mM) were added. The mixture then became colorless, and after stirring for 90 minutes (700 rpm), 0.2 volumes of hydrochloric acid (37wt% in water, 12.1M) were added to adjust the pH value of the mixture. After stirring slowly for another 15 minutes (400 rpm), 0.1-0.2 volumes of ascorbic acid (64mM) were added, stirred vigorously, and finally 0.01-0.02 volumes of gold seed solution were injected into the growth solution. After further vigorous stirring, the resulting mixture was kept at 30°C for 12 hours to grow gold nanorods. The final product was separated by centrifugation at 8000 rpm for 15 minutes, and then the supernatant was removed.
[0048] Synthesis of gold nanorod-titanium dioxide all-inclusive composite nanostructures:
[0049] Dilute 0.04-0.05 volume of 15% TiCl3 with 0.8-1 volume of deoxygenated water in a 5 volume reaction bottle (different suppliers or batches may affect the subsequent dosage). Add 1M NaHCO3 dropwise to the diluted TiCl3 solution while stirring. After the mixture turns into a blue solution, add the last 5-8 drops of NaHCO3. After that, dilute the mixture (0.1 volume of gold nanorod stock solution with deoxygenated water after centrifugation (8000 rpm) to 0.4 volume and 0.1 volume of 0.2M C 14 TAB solution) was added to the above dark blue solution. The dispersion was then gently stirred / shaken for more than one hour. The product was collected by centrifuge for 10 minutes and washed once with ethanol and then with C 16 The samples were washed once with TAB solution (0.1 M) and finally stored at C 16 TAB solution.
[0050] Modification of composite nanostructures with fluorescent molecules:
[0051] The composite nanoparticles synthesized above are modified with fluorescent molecules ENBS-PEG-SH, PEG-SH and PEG-COOH for later use.
[0052] Example 3
[0053] A specific method for synthesizing composite nanoparticles for synergistic photothermal and photodynamic therapy of hypoxic tumors.
[0054] Synthesis of gold nanorods:
[0055] 10 Volume C 16TAB (0.1M) solution was mixed with 0.1 volume of chloroauric acid solution (25mM) in a 20 volume reaction bottle, and then stirred at room temperature for 5 minutes, and 1 volume of freshly prepared 100mM NaBH4 solution (ice-cooled) was added and quickly injected into the solution mixture. The solution was rapidly stirred for 2 minutes and allowed to stand at room temperature for aging.
[0056] 7.2 g C 16 TAB was dissolved in 200 volumes of deionized water (50°C) to prepare a growth solution for gold nanorods in a 250 volume conical flask. After cooling to 30°C, 10 volumes of silver nitrate (4mM) were added. The mixture was kept at 30°C for 15 minutes, and then 20 volumes of chloroauric acid solution (1mM) were added. The mixture then became colorless, and after stirring for 90 minutes (700 rpm), 1.72 volumes of concentrated hydrochloric acid were added to adjust the pH value of the mixture. After another 15 minutes of slow stirring (400 rpm), 1 volume of ascorbic acid (64mM) was added, stirred vigorously for 30 seconds, and finally 0.64 volumes of gold seed solution were injected into the growth solution. After another 30 seconds of vigorous stirring, the resulting mixture was kept at 30°C for 12 hours for gold nanorod growth. The final product was separated by centrifugation at 8000 rpm for 15 minutes, and then the supernatant was removed.
[0057] Synthesis of gold nanorod-titanium dioxide asymmetric composite nanostructures:
[0058] Dilute 0.4 ml of 15% TiCl3 with 8 volumes of deoxygenated water in a 50 volume reaction bottle (different suppliers or batches may affect the subsequent dosage). Add 1M NaHCO3 dropwise to the diluted TiCl3 solution while stirring. After the mixture turns into a dark blue solution, add the last two or three drops of NaHCO3. After that, dilute the mixture (1 volume of gold nanorod stock solution with deoxygenated water after centrifugation (8000 rpm) to 3.6 volumes and 1 volume of 0.2M C 14 TAB solution was added to the dark blue solution. The dispersion was then gently stirred / shaken for 30 minutes. The product was collected using a centrifuge at 6000 rpm for 10 minutes and washed once with ethanol and then washed with C 16 The samples were washed once with TAB solution (0.1 M) and finally stored at C 16 TAB solution.
[0059] Modification of composite nanostructures with fluorescent molecules:
[0060] The composite nanoparticles synthesized above are modified with fluorescent molecules ENBS-PEG-SH, PEG-SH and PEG-COOH for later use.
[0061] Example 4
[0062] A specific method for synthesizing composite nanoparticles for synergistic photothermal and photodynamic therapy of hypoxic tumors.
[0063] Synthesis of gold nanorods:
[0064] 10 Volume C 16 TAB (0.1M) solution and 0.1 volume of chloroauric acid solution (25mM) were mixed in a 20 volume reaction bottle, and then stirred at 30°C for 5 minutes, and 1 volume of freshly prepared 100mM NaBH4 solution (ice-cooled) was added and quickly injected into the solution mixture. The solution was rapidly stirred for 2 minutes and allowed to stand at 30°C for 30 minutes for aging.
[0065] 14.4 g C 16 TAB was dissolved in 200 volumes of deionized water (50°C) to prepare a growth solution for gold nanorods in a 500 volume conical flask. After cooling to 30°C, 20 volumes of silver nitrate (4mM) were added. The mixture was kept at 30°C for 15 minutes, and then 40 volumes of chloroauric acid solution (1mM) were added. The mixture then became colorless, and after stirring for 90 minutes (700 rpm), 3.44 volumes of hydrochloric acid (37wt% in water, 12.1M) were added to adjust the pH value of the mixture. After another 15 minutes of slow stirring (400 rpm), 2 volumes of ascorbic acid (64mM) were added, stirred vigorously for 30 seconds, and finally 1.28 volumes of gold seed solution were injected into the growth solution. After another 30 seconds of vigorous stirring, the resulting mixture was kept at 30°C for 12 hours for gold nanorod growth. The final product was separated by centrifugation at 8000 rpm for 15 minutes, and then the supernatant was removed.
[0066] Synthesis of gold nanorod-titanium dioxide asymmetric composite nanostructures:
[0067] Dilute 0.4 ml of 15% TiCl3 with 16 volumes of deoxygenated water in a 50 volume reaction bottle (different suppliers or batches may affect the subsequent dosage). Add 1M NaHCO3 dropwise to the diluted TiCl3 solution while stirring. After the mixture turns into a dark blue solution, add the last two or three drops of NaHCO3. After that, dilute the mixture (2 volumes of gold nanorod stock solution with deoxygenated water after centrifugation (8000 rpm) to 7.2 volumes and 2 volumes of 0.2M C 14 TAB solution was added to the dark blue solution. The dispersion was then gently stirred / shaken for 30 minutes. The product was collected using a centrifuge at 6000 rpm for 10 minutes and washed once with ethanol and then washed with C 16 The samples were washed once with TAB solution (0.1 M) and finally stored at C 16 TAB solution.
[0068] Modification of composite nanostructures with fluorescent molecules:
[0069] The composite nanoparticles synthesized above are modified with fluorescent molecules ENBS-PEG-SH, PEG-SH and PEG-COOH for later use.
[0070] The gold nanorod-titanium dioxide asymmetric composite nanostructure and the gold nanorod-titanium dioxide fully encapsulated composite nanoparticles were dispersed in an aqueous solution to prepare a 5 mg / volume solution. Test solutions of different concentrations were prepared as needed to detect changes in their absorption spectra.
[0071] Example 5
[0072] Absorption spectra of gold nanorods and gold nanorod-TiO2 asymmetric composite nanoparticles and potential changes upon surface modification.
[0073] Will Figure 3 Gold nanorods and gold nanorod-titanium dioxide asymmetric composite nanoparticles were detected by UV-visible spectrophotometer. Figure A shows that the absorption spectrum of gold nanorods is around 780nm. After modification with titanium dioxide, the absorption spectrum of nanorods is red-shifted to around 810nm. PEG was modified by substitution in aqueous solution to remove the surface C 16 TAB, this process is accompanied by a gradual decrease in potential. Figure 3 B) It can be proved that the potential of the nanoparticles does gradually decrease after being gradually modified with PEG-SH, PEG-COOH, and ENBS-PEG-SH.
[0074] Example 6
[0075] Photothermal and reactive oxygen generation properties of the gold nanorod-titanium dioxide asymmetric composite nanorod.
[0076] Gold nanorods and asymmetric composite nanostructures were placed in aqueous solution (100 μg / mL) and illuminated using a laser at 808 nm and 800 mW / cm 2 The laser is used for illumination, and the real-time temperature is collected by an infrared camera. Figure 4 At 9 minutes, the temperature of the gold nanorods can rise to over 70°C, while the temperature of the nanoparticles is only 48°C. The singlet oxygen and hydroxyl radicals generated by subsequent light irradiation were captured by adding 2,2,6,6-tetramethylpiperidine and 2,2-dimethylpyrroline nitrogen oxide to the aqueous solution, and then tested with an electron paramagnetic resonance instrument. Figure 4 The electron paramagnetic resonance spectrum measured in B shows that the nanoparticles can produce a large amount of hydroxyl radicals and a small amount of singlet oxygen with hydrogen peroxide under 808nm light.
[0077] Example 7
[0078] Uptake time of gold nanorod-titanium dioxide asymmetric composite nanoparticles by human breast cancer cells.
[0079] Fluorescent FITC was modified on the surface of nanoparticles by PEG for tracing in cells. The nanoparticles modified with fluorescent groups were added to the culture medium and incubated in a carbon dioxide incubator. Cell imaging was performed using an inverted fluorescence microscope at 0, 15, 30, 45, 60, 75, and 90 minutes. Figure 5 The uptake of the nanoparticles by human breast cancer cells changes over time. It can be found that the uptake reaches the maximum at 60 minutes. After another 30 minutes of observation, the uptake hardly changes, indicating that the uptake of the nanoparticles by human breast cancer cells can reach the maximum in about 1 hour.
[0080] Example 8
[0081] The killing effect of gold nanorod-titanium dioxide all-inclusive nanostructures and gold nanorod-titanium dioxide asymmetric composite nanostructures on human breast cancer cells.
[0082] The gold nanorod-titanium dioxide all-inclusive nanostructure was mixed into the cell culture medium and used for cell incubation in a carbon dioxide incubator. After incubation for 2 hours, the supernatant was removed, the cells were washed twice with phosphate buffered saline, and then replaced with new culture medium, and then irradiated with light (808nm, 800mW / cm 2 , 10min), and then placed in an incubator for 24 hours, and then added with a medium containing thiazolyl blue (0.5mg / volume), and continued to incubate for another 4 hours. Then carefully remove the solution in the 96-well plate, dissolve the crystals with DMSO, and measure the absorbance of each well with an enzyme-labeled instrument. The processed data is shown in Figure 6 As shown in A, it can be found that the gold nanostructure fully covered by titanium dioxide has almost no killing effect on cells. In the presence of 2% oxygen, other conditions remain the same, and the gold nanorod-titanium dioxide asymmetric composite nanostructure is tested. Figure 6 In B, the phototoxic effect on human breast cancer cells under hypoxic conditions was good (cell survival rate was about 10%), while the survival rate of cells without illumination was above 80%, indicating that the nanoparticles had good biocompatibility and cell killing effect after modification.
[0083] Example 9
[0084] The nanoparticles guided the location and timing of tumor imaging in mice.
[0085] Tumor implants were established by subcutaneously injecting mice with 5×106-1×107 cells suspended in 100 μL PBS. After 7 days, when the tumor volume reached approximately 90-100 mm 3 , and subsequent experiments were conducted on tumor-bearing mice. In order to better guide the location of light therapy at the tumor location and minimize damage to surrounding normal tissues, azoamino Nile blue was modified on the surface of the nanoparticles. In vivo experiments were performed by injecting azoamino Nile blue and PEG-modified nanoparticles through the tail vein. After the nanoparticles were modified with azo ENBS, the nanoparticles reached the tumor, and azo cleavage occurred at the hypoxic tumor, thereby releasing fluorescent molecules that can be used for fluorescence imaging at the tumor to guide the light location of subsequent photothermal-photodynamic therapy. Figure 7 The fluorescent dye ENBS is modified on the surface of the nanoparticles through an azo bond. When the nanoparticles modified with the fluorescent dye reach the acidic tumor microenvironment, the azo bond connecting the dye will be broken, and the fluorescent molecule will fluoresce at the tumor. The results show that within 12 hours, under the excitation of 633nm light, it can be observed that the enrichment of the modified fluorescent nanoparticles in the tumor reaches the maximum value, which can be used to accurately guide the time and location of near-infrared light irradiation. (The mice in this experiment were purchased from the SPF Laboratory Animal Center of Dalian Medical University. This study was conducted in accordance with the "Guide for the Care and Use of Laboratory Animals" published by the National Institutes of Health. The animal experiment protocol was approved by the local research ethics review committee, the Animal Ethics Committee of Dalian University of Technology (ethical approval number is 2018-043).)
[0086] Example 10
[0087] Photothermal imaging of the nanoparticles at the tumor site in a mouse.
[0088] The mice were accurately illuminated with near-infrared light in the second region (808 nm, 800 mW / cm 2 ,10min) treatment. Figure 8 It can be found that the light temperature of the gold nanorods can reach about 55°C, while the temperature of the asymmetric nanoparticles is only 44°C. The temperature reached by the asymmetric nanoparticles can have a good killing effect on tumors without damaging the normal tissues around the tumors.
[0089] Embodiment 11
[0090] The therapeutic effect of the nanoparticles on tumors in mice and the monitoring of mouse weight.
[0091] The tumor volume of the mice was measured every two days. Fig. 9The following are the tumor change curves and weight changes of mice in different experimental groups. By comparing the tumor volumes of different experimental groups, it can be found that the asymmetric nanostructure has a better inhibitory effect on tumors, and compared with the photothermal therapy of gold nanorods alone, this photothermal and photodynamic synergistic therapy mode also has the effect of preventing tumor recurrence. And the weight of mice has basically not changed, indicating that the nanostructure is relatively safe and low-toxic.
[0092] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited by the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. A method for synthesizing an asymmetric nanocomposite material of titanium dioxide-gold nanorods, characterized in that: The nanocomposite material uses one end of the gold nanorod as the growth point of the titanium dioxide nanoparticles, so that the titanium dioxide directly contacts the one end of the gold nanorod and has an asymmetric structure, wherein the aspect ratio of the gold nanorod is 2.5-3.5, and the thickness of the directly contacted titanium dioxide is 7-20 nanometers; the surface of the titanium dioxide-gold nanorod asymmetric nanocomposite material is PEG-modified, and is also modified by a fluorescent molecule emitting at 650-900 nanometers through an azo bond; The fluorescent molecules include: cyanine dyes, semi-cyanine dyes, Nile blue, methylene blue, and rhodamine dyes; The specific steps include: (1) C 16 TAB was mixed with chloroauric acid solution, and then NaBH4 solution was injected, and the gold seed solution was obtained after standing and aging; (2) C 16 After TAB is dissolved, silver nitrate, chloroauric acid, concentrated hydrochloric acid, and ascorbic acid are added one by one, and after stirring evenly, a gold nanorod growth solution is prepared; (3) injecting the gold seed solution into the gold nanorod growth solution, mixing overnight and separating to obtain gold nanorods with an aspect ratio of 2.5-3.5 and a diameter of 10-20 nanometers; (4) NaHCO3 was added dropwise into the diluted TiCl3 solution to obtain a Ti solution, and then the gold nanorods and C 16 The TAB mixture is added to the above Ti solution to react and obtain a final product, which is an asymmetric structure in which the above titanium dioxide is directly grown on one end of the gold nanorod, wherein the aspect ratio of the gold nanorod is about 2.5-3.5, the thickness of the directly contacted titanium dioxide is 7-20 nanometers, and finally stored in C 16 TAB solution.
2. The method for preparing the asymmetric nanocomposite material of titanium dioxide-gold nanorods according to claim 1, characterized in that: The step (1) of preparing the gold seed solution in the method comprises: adding 5-20 volumes of C 16 The TAB solution is mixed with 0.1-3 volumes of chloroauric acid solution with a concentration of 10-50 mM, and then 0.6-1.2 volumes of NaBH4 solution are quickly added under stirring and the mixture is allowed to stand for aging to obtain a gold seed solution.
3. The method for preparing the asymmetric nanocomposite material of titanium dioxide-gold nanorods according to claim 1, characterized in that: The step (2) of preparing the gold nanorod growth solution in the method comprises: adding a certain amount of C 16 TAB is dissolved in 50-1000 volumes of deionized water. After cooling, 2-10 volumes of silver nitrate with a concentration of 1-10 mM are added; after stirring the mixture, 5-20 volumes of 0.5-2 mM chloroauric acid solution are added; then the mixture becomes colorless, and after stirring, 0-2 volumes of concentrated hydrochloric acid are added to adjust the pH value of the mixture; after slowly stirring, 0.2-0.8 volumes of ascorbic acid with a concentration of 40-100 mM are added and stirred vigorously.
4. The method for preparing the asymmetric nanocomposite material of titanium dioxide-gold nanorods according to claim 1, characterized in that: The step (3) of preparing gold nanorods in the method comprises: injecting 0.2-0.5 volume of the gold seed solution prepared in step (1) into the gold nanorod growth solution prepared in step (2); after a short period of intense stirring, leaving the resulting mixture overnight to obtain a gold nanorod stock solution; and centrifuging to obtain the gold nanorods.
5. The method for preparing the asymmetric nanocomposite material of titanium dioxide-gold nanorods according to claim 1, characterized in that: The step (4) of preparing the final product in the method comprises: diluting 0-0.5 ml of 10-30% TiCl3 with 2-15 volumes of deoxygenated water; adding 0.5-2 M NaHCO3 dropwise to the diluted TiCl3 solution under stirring; after the mixture turns into a blue solution, adding the last few drops of excess NaHCO3, centrifuging 0.1-2 volumes of the gold nanorod stock solution with deoxygenated water to dilute it to 0.1-1.8 volumes, and mixing it with 0.1-3 volumes of 0.2 M C 14 Mix the TAB solution; then add it to the above blue solution; gently stir / shake the dispersion for more than 1 hour; centrifuge and wash to obtain the final product, and store it in C 16 TAB solution.
6. The method for preparing the asymmetric nanocomposite material of titanium dioxide-gold nanorods according to claim 1, characterized in that: The method also includes modifying the surface of the final composite nanostructure obtained in step (4) by using an azo bond to emit fluorescent molecules at 650-900 nanometers.
7. Use of the nanocomposite material prepared by the method of claim 1 in preparing a product for photothermal and photodynamic synergistic treatment of hypoxic tumors.
Citation Information
Patent Citations
Composite gold nanorod carrier having photo-thermal / photodynamic therapy treatment performance and preparation method thereof
CN106267202A
Mushroom-structured gold nanorod-nano titanium oxide photocatalytic material and preparation method and application thereof
CN106824184A